INFLUENCE OF HYDROGEOLOGICAL SETTING ON PEATLAND BURN SEVERITY - Hokanson, Kelly J. (My University, 2014)
Organic soil depth of burn in Canadian boreal peatlands cited in the literature generally ranges from 0.05 to 0.10 m despite fire manager reports that suggest higher burn severity (> 0.50 cm) may exist on the landscape. It was hypothesized that hydrogeological setting imposes different landscape patterns of peat bulk density and moisture content leading to greater variability in organic soil burn severity across the landscape than previously thought. To examine this, depth of burn was measured in three peatlands located along a hydrogeological and topographic gradient that were affected by the May 2011 Utikuma Complex forest fire (SWF-057, ~90,000 ha) in Canada’s Western Boreal Plain. The results demonstrate that peatland margins, due to fluctuating water tables, burned significantly deeper (0.25 ± 0.01 m) than the middle (0.06 ± 0.01 m) of peatlands. Additionally, in a coarse textured glaciofluvial outwash, a bog with ephemeral groundwater connections had the greatest depth of burn (0.51 ± 0.02 m) and a low-lying flow-through bog had the lowest burn severity (0.07 ± 0.03 m). An expansive peatland in the lacustrine clay plain showed an intermediate depth of burn (0.16 ± 0.01 m). To further investigate the role of groundwater connectivity in the outwash, GWC and smouldering energy dynamics were modelled at several unburned peatlands across a topographic gradient. It was shown that the peatland with the most groundwater connectivity showed the lowest vulnerability, while the ephemerally perched peatland was the most vulnerable. The peatland at the highest topographic position and least groundwater connection showed intermediate vulnerability. This research indicates that groundwater connectivity and subsequent influence on water table fluctuations in peatland margins can have a dominant control on soil carbon combustion, it is therefore suggested that a hydrogeological ‘template’ be used to identify deep burning ‘hotspots’ on the landscape a priori, so as to increase the efficacy of wildfire mitigation strategies.
Keywords: peatland; wildfire; carbon; boreal; organic soil; hydrogeology; Hydrology; Hydrology